2022
DOI: 10.3389/fpls.2022.923219
|View full text |Cite
|
Sign up to set email alerts
|

How Do Taxonomic and Functional Diversity Metrics Change Along an Aridity Gradient in a Tropical Dry Forest?

Abstract: Ecological indicators based on biodiversity metrics are valuable and cost-effective tools to quantify, track and understand the effects of climate change on ecosystems. Studying changes in these indicators along climatic gradients in space is a common approach to infer about potential impacts of climate change over time, overcoming the limitations of lack of sufficiently long time-series data. Here, we studied the response of complementary biodiversity metrics in plants: taxonomic diversity (species richness a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 67 publications
(92 reference statements)
1
4
0
Order By: Relevance
“…As we used response diversity as an indicator of the resilience of the functional groups [45], we can state that the resilience of all groups has eroded since the great drought. Oliveira [87] showed that communities in drier sites along an aridity gradient in a South American dry forest presented a smaller functional redundancy and are therefore less resilient, which is supported by our results. Several research studies have shown the negative effects of the great drought on woody populations in terms of density and species' composition [15,21,29,88].…”
Section: Evolution Of Functional Redundancy and Response Diversity Fr...supporting
confidence: 88%
“…As we used response diversity as an indicator of the resilience of the functional groups [45], we can state that the resilience of all groups has eroded since the great drought. Oliveira [87] showed that communities in drier sites along an aridity gradient in a South American dry forest presented a smaller functional redundancy and are therefore less resilient, which is supported by our results. Several research studies have shown the negative effects of the great drought on woody populations in terms of density and species' composition [15,21,29,88].…”
Section: Evolution Of Functional Redundancy and Response Diversity Fr...supporting
confidence: 88%
“…Our study also provides evidence that some facets of diversity, such as functional diversity, may respond differently to seasonal variations in environmental conditions. Studies with different biological groups in distinct ecosystems have shown that other facets of diversity can react differently to environmental stressors (Correa & da Silva, 2022; De Pauw et al, 2021; Oliveira et al, 2022; Rivera et al, 2022). This result reinforces the need to investigate more than one facet of diversity to obtain a more robust picture of species responses to environmental changes (Devictor et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Such loss can be translated into broader alteration of ecosystem function and effects on important ecosystem services such as nutrient recycling, carbon sequestration, and many others. In developing trait-based approaches to monitor chemical impacts on ecosystems, basic challenges include which traits are most relevant for ecosystem function and what metrics can be used to characterize alterations in those traits. , Indicators for functional diversity include measures of functional redundancy (i.e., analogous traits in different species of an ecosystem that contribute to the same ecosystem function), and direct field-based measurements of ecosystem functions are frequently used to characterize changes in ecosystem traits. For example, oxygen concentrations can be monitored to approximate respiration rates in rivers and streams, while leaf-litter breakdown rates and microbial activity can be monitored to assess functional integrity of streams based on how leaves are processed by stream communities .…”
Section: The Need For Computational Methods To Assess Chemical Impact...mentioning
confidence: 99%